Measuring Financial Market Integration over the Long Run: Is there a U-Shape? - Vadym Volosovych (Tinbergen Institute, 2011)
Using long time series for sovereign bond markets of fifteen industrialized economies from 1875 to 2009, I find that financial market integration by the end of the 20th century was higher than in earlier periods and exhibited a J-shaped trend with a trough in the 1920s. The main reason for the higher financial integration seen today is the recent extensive globalization. Around the turn of the 20th century, countries frequently drifted apart. Conversely, in recent years, the bond markets of most countries have moved together. Both policy variables and the global market environment play a role in explaining the time variation in integration, while 'unexplained' changes in the overall level of country risk are also empirically important. My methodology, based on principal components analysis, is immune to outliers and accounts for global and country-specific shocks and, hence, can capture trends in financial integration more accurately than standard techniques such as simple correlations.
Keywords: F02; F36; G15; N20; 330; financial markets integration; principal components; sovereign bonds; Öffentliche Anleihe; Finanzmarktregulierung; Marktintegration; Hauptkomponentenanalyse; Schätzung; Welt